MUTU PEMIMPIN DALAM PENINGKATAN PELAYANAN DI KLASIS GPDPB KOTA SORONG: THE QUALITY OF LEADERS IN IMPROVING SERVICES IN THE GPDPB CLASS, SORONG CITY - Yulian Anouw; Nelson Naa (EIRENE (JURNAL ILMIAH TEOLOGI), 2023)
Abstract: The servant of God in his role as a leader in the Classical Pentecostal Church of Sorong City needs to realize quality leadership in ministry through Bible teaching and spiritual development for the congregation towards service improvement that has a positive impact on faith growth. But in reality the leaders are still lacking in increasing the ministry of faith growth as expected together in church ministry. This research was conducted to determine the factors causing the lack of service improvement by leaders and also to find out how qualified leaders are in service improvement. The method in this study is a qualitative method, a population of 100 people and a sample of 30 people, with the technique of observation, literature study and interviews. The results of this study are leaders are more optimal in realizing service improvements that have an impact on the development and growth of faith and also leaders must improve the quality of their personalities as leaders through increasing theological knowledge both formally and informally so that services are more effective towards church development and faith growth. Abstrak: Hamba Tuhan dalam peranan sebagai pemimpin di Gereja Pentakosta Klasis Kota Sorong perlu mewujudkan kepemimpinan yang bermutu dalam pelayanan melalui pengajaran Alkitab dan pembinaan rohani bagi jemaat menuju peningkatan pelayanan yang berdampak positif terhadap pertumbuhan iman. Namun pada kenyataannya pemimpin masih kurang dalam meningkatkan pelayanan pertumbuhan iman seperti yang diharapkan bersama dalam pelayanan gereja. Penelitian ini dilakukan untuk mengetahui faktor penyebab kurangnya peningkat pelayanan oleh pemimpin dan juga untuk mengetahui bagaimana pemimpin yang bermutu dalam peningkatan pelayanan. Metode dalam penelitian ini adalah metode kualitatif, populasi 100 orang dan sampel 30 orang, dengan teknik observasi, studi pustaka dan wawancara. Hasil dari penelitian ini adalah pemimpin lebih maksimal dalam mewujudkan peningkatan pelayanan yang berdampak kepada perkembangan dan pertumbuhan iman dan juga para pemimpin harus meningkatkan mutu kepribadiannya sebagai pemimpin melalui peningkatan pengetahuan teologi baik secara formal dan non formal agar pelayanan lebih efektif menuju perkembangan gereja dan pertumbuhan iman..